Building Inclusive Education Systems: Early Intervention and a Three-Tiered Support Framework for Diverse Learners - Das, Soma Bepari (Journal of Research in Vocational Education, 2026)
Unique abilities and challenges, preferences and dreams reflect one’s individuality. This individuality needs respect and an unconditional acceptance in the society, specifically in the education world. All stakeholders involved in the development of a child need to be involved right from the beginning with an understanding that each child has strengths which need to be celebrated and not problems to be solved. This paper is a small step towards creating welcoming communities, combating discriminatory attitudes, building inclusive society, and achieving education for all. The challenge is to create responsible universal citizens and influential individuals of the 21st century. This can be realized by laying a superior foundation through quality education embedded within the psychological well - being of all the learners. Every individual strives to receive a well - rounded educational programme irrespective of the diverse intellectual, social, emotional, and physical needs. Early intervention and prevention focus on a wide range of learners including able, gifted, talented, and special educational needs. Three - tiered intervention ensures maximum benefits for all learners to ensure a life with respect, dignity, care, and highest level of functioning. It involves understanding and addressing the mental health concerns and diverse levels of need among learners and families within the school community. This model aids in looking beyond the challenges through intervention at three levels primary, secondary, and tertiary. Implementing early intervention and prevention among the school community mitigates the development of behavioural, emotional, and academic problems and concerns of the learners.